2021
DOI: 10.1155/2021/6696015
|View full text |Cite
|
Sign up to set email alerts
|

Brusatol Inhibits Tumor Growth and Increases the Efficacy of Cabergoline against Pituitary Adenomas

Abstract: Cabergoline (CAB) is the first choice for treatment of prolactinoma and the most common subtype of pituitary adenoma. However, drug resistance and lack of effectiveness in other pituitary tumor types remain clinical challenges to this treatment. Brusatol (BT) is known to inhibit cell growth and promote apoptosis in a variety of cancer cells. In our present studies, we investigate the effects of BT on pituitary tumor cell proliferation in vitro and in vivo. BT treatment resulted in an increase in Annexin V-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In agreement with our findings, a study conducted on NSCLC cells revealed a possible association between brusatol and the modulation of ROS-mediated mitochondrial-dependent pathways together with the inhibition of an antioxidant response mediated by NRF2 inhibition [ 12 ]. In another study, the promotion of ROS and NRF2 suppression by brusatol resulted in a growth inhibition of lung cancer and pituitary cancer cells both in vitro and in vivo [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, a study conducted on NSCLC cells revealed a possible association between brusatol and the modulation of ROS-mediated mitochondrial-dependent pathways together with the inhibition of an antioxidant response mediated by NRF2 inhibition [ 12 ]. In another study, the promotion of ROS and NRF2 suppression by brusatol resulted in a growth inhibition of lung cancer and pituitary cancer cells both in vitro and in vivo [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the inhibition of the mTORC1 pathway is involved in the inhibition of PitNET growth [39]. The Brusatol-induced inhibition of the mTORC1 signaling pathway leads to inhibition of tumor growth in PitNETs [40]. Rapamycin and RAD001, which are mTOR inhibitors, potently inhibit pituitary cell proliferation in GH3 cells [41].…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, Bru was considered as an unparalleled inhibitor of the Nrf2 pathway, exhibiting growth inhibition and pro-apoptotic effects in a variety of cancer cells ( Evans et al, 2018 ; Cai et al, 2019 ). By promoting ROS production and down-regulating Nrf2 expression, Bru significantly inhibited the growth of lung cancer and pituitary tumor cells in vitro and in vivo ( Sun et al, 2016 ; Wu et al, 2021 ). Similar results were also shown in the field of glioma treatment ( Tang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%